ANALISIS PENGARUH PROFITABILITAS, SUKU BUNGA, LIKUIDITAS, DAN SOLVABILITAS TERHADAP PREMI BRUTO ASURANSI DI INDONESIA PADA TAHUN 2012-2016 - Chusnul Chabibah Ilhama; M Faisal Abdullah (Program Studi Ekonomi Pembangunan, 2018)
This research aims to analyze the effect of profitability, interest rates, liquidity, and solvency on insurance gross premium in Indonesia. The financial ratios studied are Return on Assets, Current Assets Ratios, and Debt to Equity Ratio as independent variables and demand for insurance services as the dependent variable. The data in this study used secondary data for five years (2012-2016), to analyze this study using multiple linear regression analysis with the data used is panel data which then carried out hypothesis testing with F test, T test, and Determination Coefficient (R- Square). The results of panel data regression analysis with the selected model are Fixed Effect Model which shows that the variables of profitability, level of liquidity, and solvency level have an influence on the demand for insurance services in Indonesia. While the interest rate shows no effect on the demand for insurance services in Indonesia. The results of this analysis show the following profitability (X1) 13.73, liquidity (X2) -2.4, solvency (X3) 2.28 and Interest Rate (X4) -0.83. While the value for the coefficient of determination (R-Square) is 0.87 or 87%. This shows that the variable capability of profitability, interest rates, liquidity, and solvency in explaining the demand for insurance services in Indonesia is 87%. Keywords: Financial Ratio, Gross premium